CLOSTRIDIAL ENDOPHTHALMITIS: CLINICAL PRESENTATIONS, MANAGEMENT OUTCOMES, AND REVIEW OF LITERATURE. Issue Volume 16:Issues 1(2022) (January 2022) - Dave, Vivek P.; Joseph, Joveeta; Pathengay, Avinash; Pappuru, Rajeev R.; Das, Taraprasad
Abstract : Purpose: To describe the clinical presentations, diagnosis and management outcomes of clostridial endophthalmitis, and a review of the previous literature. Design: Retrospective, interventional case series from January 2005 to March 2018 and a literature review. Methods: The study included seven eyes of seven patients with culture-proven Clostridium sp. endophthalmitis. Identification of Clostridium sp. was confirmed by the VITEK 2 system using the ANC card. When VITEK failed to identify the organism, MALDI-TOF was used. Data regarding demography, clinical presentations, interventions received, and final visual and anatomical outcomes were noted. Results:The: mean age of the patients was 28.28 ± 22.35 years (median 21 years). By the etiology of infection, 5 (75%) eyes were post–open-globe injury, 1 (12.5%) was post-trabeculectomy, and 1 (12.5%) was postintravitreal injection. The mean follow-up was 9.71 ± 12.03 months, median 6 months. Two samples were positive for Clostridium perfringens, one each for C. subterminale, C. difficile, and C. tertium, and two were unidentified clostridial species. Favorable anatomical outcome was seen in 3/7 eyes (42.85%). Favorable functional outcome was seen in 2/7 eyes (28.57%). These were comparable with the outcomes of the pooled pre-existing literature. There was a trend toward better functional and anatomical outcomes and lesser evisceration/enucleation rates with vitrectomy instead of a vitreous tap, although not statistically significant. All cases showed susceptibility to empirically used intravitreal antibiotic vancomycin. Conclusion: Commonest setting of clostridial endophthalmitis is post–open-globe injury. Despite treatment with appropriate antibiotics, the visual and anatomical outcome is unsatisfactory because of high organism virulence. Early vitrectomy may allow for globe salvage and potential vision. Abstract : Although ocular wounds frequently get contaminated, the overall occurrence of clostridial intraocular infections is rare. An early diagnosis and prompt aggressive treatment may result in acceptable outcomes. In the current communication, we describe a series of cases of endophthalmitis secondary to clostridia sp. treated at our center.